Rijsttafel di Batavia: Kelas Sosial dan Pengaruh Eropa di Meja Makan pada Awal Abad ke-20 - Irma Zahrotunnisa Wijaya; Awalia Rahma (Socio Historica: Journal of Islamic Social History, 2022)
This study uses Class Taste and Life-Style analysis to explain how social class can form rijsttafel in Batavia. The problem concerns the formation and influence of rijsttafel in Batavia as a product of Indis culture on eating culture. The sources are books, photos, magazines, and contemporary newspapers. This study uses the historical method, a cultural approach traced from various sources obtained in the formation of rijsttafel in Batavia. The results show that the formation of rijsttafel in Batavia in the 20th century began with the existence of social class among European households. This formation was strongly influenced by the household environment, especially the role of nyonya, djongos and kokkie, which completed a rijsttafel formation in Batavia.Penelitian ini mengkaji bagaimana kelas sosial bisa membentuk rijsttafel di Batavia dengan menggunakan analisis Class Taste and Life-Style. Permasalahan yang dibahas adalah mengenai pembentukan dan pengaruh rijsttafel di Batavia yang merupakan produk budaya Indis terhadap budaya makan. Sumber yang digunakan adalah buku-buku, foto, majalah, surat kabar sezaman. Dengan menggunakan metode sejarah, pendekatan sosiologi budaya yang dapat dilacak dari berbagai sumber yang didapat pada pembentukan rijsttafel di Batavia. Hasilnya memperlihatkan bahwa pembentukan rijsttafel di Batavia pada abad ke-20 berawal dari adanya kelas sosial dikalangan rumah tangngga orang-orang Eropa. Pembentukan ini sangat dipengaruhi dari lingkungan rumah tangga khususnya peran nyonya, djongos dan kokkie yang menyempurnakan sebuah pembentukan rijtaffel di Batavia.